STRATEGIES FOR CLONING AND HIGHER EXPRESSION OF ASPERGILLUS FLAVUS URATE OXIDASE GENE IN E.COLI - SANKARI.N; M.VIJAYALAKSHMI; M.DECCARAMAN; R.BALASUBRAMANIAN (International Journal of Pharma and Bio Sciences, 2014)
Evolution of recombinant DNA technology led to the procession of therapeutic fields in oncology, autoimmune, diabetic, cardiovascular, more in diagnostic field to identify a specific cause, and in many sections of industrial platforms. Demand for these recombinant protein products, increasing day by day, and created the need to develop efficient expression techniques to increase the productivity with low production cost. The key factors in the development of therapeutic biologics are, starting the work with authenticated gene sequence and cost effective process development. Urate oxidase, the enzyme from Aspergillus flavus cloned in Escherichia coli, and used in the prevention and treatment of hyperuricemia associated with lymphoid malignancies. Here we depicted an optimized workflow for the cloning and high volumetric production of recombinant urate oxidase in E.coli with systematic optimization of the expression levels. The E.coli strain, Rosetta, plys S was used as the workhorse for production of recombinant urate oxidase. In the current work, we attained high expression levels (40%) with the highest wet pellet (60g/L).Parameters including confirmation of the gene orientation and other upstream parameter of the suitable OD of hosts, optimal IPTG concentration for induction, and time to harvest were studied systematically to achieve the high volumetric productivity.